PERAN NON-GOVERNMENTAL ORGANIZATION PATTIRO JAKARTA DALAM PROGRAM REHABILITASI HUTAN DAN LAHAN (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Indonesia is one of the countries that has the largest forests in the world, forests are an important element in regulating climate. Forests must be managed well because the benefits and role of forests are very important for life. However, Indonesia's forests are experiencing damage due to various factors. The government supports forest restoration activities through the Forest and Land Rehabilitation (RHL) program which consists of reforestation and reforestation activities. To realize good results in RHL activities, roles from non-governmental parties are needed, involving NGOs as new actors other than government who can help the country to resolve forestry problems and the impacts resulting from forest destruction. This research method is a literature study with primary data sources obtained when carrying out internship activities at one of the NGOs in Jakarta, namely PATTIRO and secondary data obtained through literature such as journals, books or FGDs. The results of the research are that support from parties or actors other than government can ease the burden that must be faced by the state in overcoming forestry problems. NGO PATTIRO is one that is concerned about forest problems. With three roles that NGO PATTIRO has, namely as implementer, catalyst and partner.